Interv'iu A. I. Solzhenitsyna TRK "Ostankino" . Interv'iu A. I. Solzhenitsyna TRK "Ostankino" . Interview of Aleksandr Solzhenitsyn to the TV-Radio Company "Ostankino" . Интервью А. И. Солженицына ТРК "Останкино" - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with Aleksandr Solzhenitsyn about the military revolt in Moscow on October 3-4 and the forthcoming elections for the Federal Assembly of the Russian Federation. Contributors: Kondrat'ev, Vladimir (Anchor) Интервью с Александром Солженициным о военном мятеже 3-4 октября 1993 года в Москве и предстоящих выборах в Федеральное Собрание Российской Федерации. Создатели: Кондратьев, Владимир (Ведущий/Ведущая)